Comportamento espacial da cultura canavieira no Estado de Sao Paulo, 1980 - Dos Santos, M. J Z (My University, 1989)
Data from the agricultural and Cattle Raising Census for 1980 show that most of the sugar cane producing counties lie in the administrative regions of Campinas, Ribeirao Preto and Sao Jose do Rio Preto. A comparison with the 1975 data shows two important facts; 1) an increase of the cultivated area in 118 counties and 2) an increase in the number of counties with area under sugar cane. There was also an expansion in the sub-regions of Catanduva, Assis and Ourinhos. Nevertheless, Piracicaba, Araraquara, Ribeirao Preto, Jaboticabal and Jau, have continued to be important sugar cane producing nuclei in the State since 1960. -from English summary
Spatial distribution of sugar cane in the state of Sao Paulo, 1980
Keywords: crop distribution study; sugar can production; Brazil, Sao Paulo State